Depiction of a four-armed Goddess seated on a lotus seat - Temples of India Project Team (Jio Institute, 2024)
The sukanasa (antefix above the roof of the kapila) is placed above the antarala (vestibule or antechamber) which serves as the frontal pediment of the garbhagriha’s (sanctum sanctorum) shikhara (superstructure). The southern side of the sukanasa is carved with a distinct scene depicting a miniature balcony where three beautiful women are shown talking to each other. Above the balcony, an udgama (pediment of interconnected chaitya dormers) is placed, depicting a four-armed Goddess seated on a lotus seat, flanked by two attendants.